ENHANCEMENT LEARNING AKSI PLATFORM READING LITERACY OF ELEMENTARY STUDENTS - Muhammad Faisal; Latri Aras; Winda Tri Astuti Rahman (Universitas Negeri Makassar, 2023)
This research is experimental research that aims to find out: a description of the usage platform AKSI (Advance Knowledge and Skills for Sustainable Growth in Indonesia) for learning and improving students' reading literacy. This type of research is called Quasi-Experimental Design using the design Nonequivalent Control Group. The sample in this study amounted to 63 people. Research data collection techniques used are observation, tests, and documentation. Data analysis techniques use descriptive and inferential techniques. The results of the descriptive analysis show that platform AKSI learning was carried out very well and student activity in the learning process was also very good. As for the student's reading literacy skills, the results of the posttest in the experimental class showed a fairly high category of reading literacy ability. Based on the results of inferential statistical analysis, P = 0.002 is smaller than α = 0.05. Based on this it can be concluded that there is an influence of platform learning from AKSI on increasing reading literacy for class IV UPT SPF SDN Unggulan Mongisidi 1 Makassar.